ANALISIS WACANA KRITIS MODEL NORMAN FAIRCLOUGH PADA LAMAN BABAD.ID TENTANG PERGANTIAN KE KURIKULUM MERDEKA - Elsa Sabrina Br Barus; Joeyakin Christo Manik; Lastri Sintauli Siahaan; Nuraini Nuraini; Fitriani Lubis (IdeBahasa, 2023)
This study aims to analyze the article "Merdeka Curriculum, change the minister change the curriculum? Here's the explanation of Kemendikbudristek "published by Babad.id on July 6, 2022. The article describes the agreement between the government and the public on the currency policies that are constantly changing as the turn of the Minister of Education and Culture. This research uses qualitative descriptive research method. Data in this study were collected using read methods, check, and recorded. Through a critical wacana analysis of the Norman fairclough model, researchers found that the article contained four news representations and three practice of wacana analysis that influenced the public's view on curriculum policies.